2018
DOI: 10.1016/j.aop.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Gross–Neveu–Wilson model and correlated symmetry-protected topological phases

Abstract: We show that a Wilson-type discretization of the Gross-Neveu model, a fermionic N-flavor quantum field theory displaying asymptotic freedom and chiral symmetry breaking, can serve as a playground to explore correlated symmetry-protected phases of matter using techniques borrowed from high-energy physics. A large-N study, both in the Hamiltonian and Euclidean formalisms, yields a phase diagram with trivial, topological, and symmetry-broken phases separated by critical lines that meet at a tri-critical point. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 141 publications
2
79
1
Order By: Relevance
“…2 (a). We note that a similar splitting of a c = 1 massless Dirac fermion into a couple of c = 1/2 massless Majoranas has been recently observed in other models of correlated SPT phases with instantaneous Hubbard-type interactions instead of the gauge-mediated ones [58][59][60]. In this section, we consider the following question: what is the fate of the SPT phase as we increase the dimension of the gauge group symmetry Z N ?…”
Section: B Lattice Discretization Of the Schwinger Modelmentioning
confidence: 69%
“…2 (a). We note that a similar splitting of a c = 1 massless Dirac fermion into a couple of c = 1/2 massless Majoranas has been recently observed in other models of correlated SPT phases with instantaneous Hubbard-type interactions instead of the gauge-mediated ones [58][59][60]. In this section, we consider the following question: what is the fate of the SPT phase as we increase the dimension of the gauge group symmetry Z N ?…”
Section: B Lattice Discretization Of the Schwinger Modelmentioning
confidence: 69%
“…(4) and by comparing h G α (k) with h S α (k), we expect that in the i-SSH model, the same mechanism leads to a modification of the parameter J 1 , that is, interaction acts as correction for the parameter J 1 , which determines the strength of the inner-bond order in the i-SSH model. Some previous studies [6,14] have expected that the CGNW model has a novel state with a non-zero expectation value ofψ α,i γ 5 ψ α,i in a large g 2 regime. This state is known as the Aoki phase, which is a parity-broken phase [5,6,14].…”
Section: Relationshipmentioning
confidence: 97%
“…Some previous studies [6,14] have expected that the CGNW model has a novel state with a non-zero expectation value ofψ α,i γ 5 ψ α,i in a large g 2 regime. This state is known as the Aoki phase, which is a parity-broken phase [5,6,14]. Then, from the relation of Eq.…”
Section: Relationshipmentioning
confidence: 97%
See 1 more Smart Citation
“…In Ref. [64], the phase diagram is studied for anistropic lattices in order to understand the result of density-matrix renormalizatoin group, and it is found that Aoki phase does not extend to the zero coupling when lattice anistropy is introduced. This is consistent with our anomaly constraint since lattice π 2 rotation is explicitly broken, which clarifies the importance of lattice symmetries.…”
Section: Aoki Phase Of 2d Lattice Gross-neveu Model With Wilson Fermionmentioning
confidence: 99%